A Novel Control Architecture for Mission Re-Planning of AUV - Rubo Zhang; Haibo Tong; Changting Shi (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A hierarchical control architecture for mission re-planning of autonomous underwater vehicle (AUV) navigating in uncertain ocean environment is presented in this paper. The proposed component-oriented control architecture structured is made of three parts: situation reasoning, re-planning trigger and hierarchical re-planning layer. Situation reasoning using the unstructured real-word information obtained by sorts of sensor detectes and recognizes uncertain event.The re-planning trigger decides the re-planning level by the event types and influence degree. Hierarchical re-planning layer contains mission re-planning, task re-planning and behavior re-planning. Different re-planning level depends on the result of re-planning trigger. Preliminary versions of the architecture have been integrated and tested in a simulation environment. Experiment indicates that the novel control architecture can implement mission re-planning steady and safty. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5442